Preparation of the Binder from Banana Pseudostem Waste and Its Application in Pigment Dyeing - Abdul Fatah Larik; Najma Memon; Rashid Hussain Memon; null Sirajuddin; Farhana Khanam Ferdousi; Ahsan Habib (Journal of Chemistry)
The disposal of banana pseudostem waste creates substantial environmental concerns. To address this issue, it is crucial to explore the potential of converting this abundant waste into valuable industrial products. Therefore, this research was designed to explore the utilization of banana pseudostem fiber waste (BPW) in the development of a textile binder. Solvothermal digestion of pseudostem fibers into ammonia followed by neutralization with sulfuric acid resulted in viscous gel which was tested as a binder (BPW-binder) for the pigment dying process. Various parameters, including curing, washing fastness, tensile strength, stiffness, and light fastness, were examined to compare the performance of the two binders. The results showed that the BPW-binder performed similarly to the commercial Halzarin binder in terms of washing fastness and did not leave any stains on the multifibre strip. Both binders demonstrated excellent light fastness, with a rating of 8 on the blue wool scale for both cotton and cotton-polyester fabrics. However, there were slight variations in elongation and stiffness between the two binders with values ranging from 9.41 to 28.26% and 1.5 to 1.9 CMS across different fabric types, which were dependent on the fabric. Fourier transform infrared analysis revealed lignin amine salt peaks in the banana pseudostem-based BPW-binder, while scanning electron microscope images of BPW-binder treated fabrics confirmed suitable binder properties with a rough and ordered lamellar surface. This study demonstrates the potential of transforming banana pseudostem fiber waste into a sustainable textile binder through an efficient and straightforward process. The BPW-binder showed comparable performance to the synthetic commercial binder, indicating its potential as a sustainable replacement in the industry.